Discourse Analysis of Nato's Intervention In Libya In 2011 - Umar Suryadi Bakry (Pelopor Publikasi Akademika, 2025)
The issue of humanitarian intervention has again become a discussion in the realm of international relations studies in connection with the outbreak of NATO military intervention in Libya in 2011. A fierce debate among both theorists and practitioners began when NATO carried out a humanitarian intervention mission into Libya by bombing Libyan military bases. This study seeks to understand the controversial events of NATO's humanitarian intervention in Libya by using an approach born after the end of the Cold War, namely constructivism. Meanwhile, the type of research used is qualitative research using discourse analysis and interpretive analysis. The results of the study show that the majority of UN member states have indeed accepted humanitarian intervention as a new norm in international relations, but this new norm has been abused by a number of countries to protect their material national interests. At least in the case of NATO's intervention in Libya, the process of accepting humanitarian intervention norms (including human rights norms and democracy) did not take place through the process of communicative action as Habermas believes. The process of accepting these new norms tends to go through a coercion approach as introduced by Wendt. Then based on the analysis of the discourse, it can be concluded that there has been a hegemony of communication by Western society, especially regarding the discourse of atrocities committed by the Gaddafi regime, so that this opens up the possibility of humanitarian intervention.